Determining horizontal well profile with side branches to ensure target operating parameters - L. G. Korshunova; A. V. Handzel; O. O. Tagirov; M. V. Krayushkina; L. N. Konovalova (Вестник Северо-Кавказского федерального университета, 2022)
There is a view on the issue of calculating gas inflow towards a multi-barrelled horizontal well in a strip bed. There is a mathematical model combining a joint solution for an equation of gas filtration in the bed and the equations to describe gas flow within the barrels of the horizontal well. There is a presentation of the results from calculation of configurations for a multi-barreled horizontal well allowing obtaining the required level of production.